Comprehensive trends and patterns of antihypertensive prescriptions using a nationwide claims database in korea - Jung, Minji; Choo, Eunjung; Lee, Sukhyang (Clinical Epidemiology, 2020)
Purpose: The number of people receiving antihypertensive prescriptions in Korea has increased more than threefold from 2002 to 2016. However, previous studies regarding the current use of these medications have been fairly limited. We aimed to examine the current trends and changes in the patterns of antihypertensive prescriptions based on a nationwide claims database. Patients and Methods: Patients receiving antihypertensive medications over 30 days, without any limited therapeutic indication, were identified using the Health Insurance Review and Assessment Service (HIRA) database between 2015 and 2017. For each patient, the use of antihypertensive medication was specified as the class of drug used for the longest duration in each year. Results: A total of 8,625,821 patients in 2015, 8,997,829 patients in 2016, and 9,357,751 patients in 2017 taking antihypertensives were included in this study. Angiotensin II receptor blockers (ARB) (35.9% in 2015 and 38.9% in 2017) and calcium channel blockers (CCB) (37.1% in 2015 and 35.2% in 2017) for monotherapy, ARB+CCB combinations (49.3% in 2015 and 56.3% in 2017) for dual therapy, and ARB+CCB+diuretics combinations (48.8% in 2015 and 48.9% in 2017) for more than triple therapy were the most frequently prescribed. Subjects aged ≥70 showed the highest prescription rate of antihypertensives compared with those <70; however, a decreasing trend presented from 62.3% in 2015 to 54.2% in 2017. Additionally, in subjects aged >70 years, the rate in women was higher than that in men, but this was reversed in younger patients. While changes arose in the patterns of the use of antihypertensives, these were similar each year. Conclusion: The trends and changes in the patterns of the use of antihypertensive medications were affected by age, sex, and type of therapy. Our findings may contribute to a better understanding of the actual status regarding the use of antihypertensive medications in Korea.
Keywords: Antihypertensive medications; Drug utilization study; Nationwide claims database